Therapeutic Applications of Targeted Alternative Splicing to Cancer Treatment - Lin, Jung-Chun (Int J Mol Sci, 2017)
A growing body of studies has documented the pathological influence of impaired alternative splicing (AS) events on numerous diseases, including cancer. In addition, the generation of alternatively spliced isoforms is frequently noted to result in drug resistance in many cancer therapies. To gain comprehensive insights into the impacts of AS events on cancer biology and therapeutic developments, this paper highlights recent findings regarding the therapeutic routes of targeting alternative-spliced isoforms and splicing regulators to treatment strategies for distinct cancers.